Houthi and Resistance against USA Dominance in the Middle East - Baihaki, Achmad (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
The crisis in Yemen has transformed into a conflict resulting in numerous casualties, damages, violence, and chaos. According to the Al-Houthi group, this crisis stems from President Ali Abdullah Saleh's corrupt practices, which have inflicted suffering on many citizens. According to a report by the Expert Panel of the World Body, President Ali Abdullah Saleh has been engaged in corruption from 1978 to 2012. Additionally, interventions from the United States have raised suspicions of hidden agendas in this conflict. From a geopolitical standpoint, this conflict holds strategic importance for the interests of the United States, leading to prolonged conflict and hindering the attainment of resolution. This research aims to analyze the conflict and resistance of the Houthi group against the interests of the United States in Yemen using qualitative methods based on secondary data